Servant leadership informed trauma peer support. Issue 4 (22nd July 2021) - Mahon, Daryl
Abstract : Purpose: Peer support has gained increasing attention within the mental health literature, including the trauma informed approaches research where peer support is a key principle. The purpose of this paper is to outline a servant leadership model of trauma peer support. Design/methodology/approach: A targeted literature search that incorporated systematic reviews, meta-analyses and randomised control trials in the areas of servant leadership, peer support and trauma informed approaches were sourced. Findings: Servant leadership can be used to provide a theoretical model of trauma peer support. All three constructs share the idea of empowerment as a core principle. An ideographic model of servant leadership trauma peer support is put forward based on eight characteristics from the extant literature. Research limitations/implications: As with all conceptual papers, a lack of empirical data means the findings need to be investigated using primary data. Future research may wish to use this theoretical model to test effectiveness in equivalence studies. Practical implications: A theoretical model of trauma informed peer support based on servant leadership theory, with a clear guide to its utilisation. Originality/value: This is a novel approach, a new addition to the literature.